2020
DOI: 10.1002/mrd.23399
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation status of bovine blastocysts obtained from peripubertal oocyte donors

Abstract: In the dairy industry, the high selection pressure combined with the increased efficiency of assisted reproduction technologies (ART) are leading toward the use of younger females for reproduction purposes, with the aim to reduce the interval between generations. This situation could impair embryo quality, decreasing the success rate of the ART procedures and the values of resulting offspring. Young Holstein heifers (n = 10) were subjected to ovarian stimulation and oocyte collection at 8, 11, and 14 months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…Maternal ART procedures such as OS and IVM were linked to a higher frequency of imprinting defects in embryos (Kindsfather et al, 2019; Market‐Velker et al, 2010; Santos et al, 2010); however, evidence in the mouse (Anckaert et al, 2013; Denomme et al, 2011; Kindsfather et al, 2019) and the bovine (Heinzmann et al, 2011) models suggest that oocyte methylation is not affected by these procedures. Similarly, methylation differences were observed in blastocysts derived from bovine oocytes of prepubertal donors of varying ages (Morin‐Doré et al, 2020). The present study provides new evidence to more accurately describe the acquisition of DNA methylation at IGF2R, KCNQ1, PLAGL1, and SNRPN bovine maternally imprinted genes and its relationship to oocyte development.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Maternal ART procedures such as OS and IVM were linked to a higher frequency of imprinting defects in embryos (Kindsfather et al, 2019; Market‐Velker et al, 2010; Santos et al, 2010); however, evidence in the mouse (Anckaert et al, 2013; Denomme et al, 2011; Kindsfather et al, 2019) and the bovine (Heinzmann et al, 2011) models suggest that oocyte methylation is not affected by these procedures. Similarly, methylation differences were observed in blastocysts derived from bovine oocytes of prepubertal donors of varying ages (Morin‐Doré et al, 2020). The present study provides new evidence to more accurately describe the acquisition of DNA methylation at IGF2R, KCNQ1, PLAGL1, and SNRPN bovine maternally imprinted genes and its relationship to oocyte development.…”
Section: Discussionmentioning
confidence: 85%
“…Differences in follicular development dynamics (Currin et al, 2021; Landry, Labrecque, et al, 2018; Landry, Rossi‐Perazza, et al, 2018; Warzych et al, 2017) result in oocytes collected from prepubertal donors to enter atresia faster than their mature donor counterparts when left in the follicle longer before OPU (Landry, Labrecque, et al, 2018; Landry, Rossi‐Perazza, et al, 2018). Moreover, molecular evidence highlighted transcriptomic (Morin‐Doré et al, 2017) and epigenetic (Morin‐Doré et al, 2020) differences between embryos derived from mature and immature oocyte donors. In a previous study, we also observed that the donor's age coupled with ART affected maternally imprinted genes in embryonic and trophoblastic cells of Days 7 and 12 embryos (Lafontaine et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the methods described above, pre-implantation bovine embryos have been studied using a variety of other tools too (Table 10). Ribosome profile High-resolution ribosome fractionation, polysome profiling, RNA-seq [198] DNA methylation landscape Anti-5-methylcytosine (5-MeC) antibody, methylation-sensitive high-resolution melting analysis (MS-HRM), bisulfite sequencing [75,[242][243][244][245][246][247][248] mRNA localization In situ hybridization [63,80,249,250] Chromosomal abnormalities 5% Giemsa staining (1250× magnification) [251] Automation/artificial intelligence (AI)-based microscopy Use of genetic algorithms, artificial neural networks, automatic feature extraction from images and supervised learning to formulate AI-based computer-assisted scoring systems (CASS)/predictive models [1,[252][253][254][255][256] Gene knockdown Cytosine base editing, CRISPR/Cas-9 gene editing, siRNA-mediated gene knockdown [79,182,196,197,257] Characterization of extracellular vesicles Nanoparticle tracking analysis, electron microscopy, small RNA sequencing [258][259][260] Multi-omics approaches Integrating transcriptomic and epigenetic data and integrating metabolomics and epigenetic data [261,262]…”
Section: Less Commonly Used Toolsmentioning
confidence: 99%
“…In mice (Zhang et al 2019) and bovine (Ispada et al 2020), the supplementation of culture media with α-KG during in vitro development interferes with DNA methylation/demethylation dynamics. Still in bovine, the analysis of the effect of the paternal and maternal age (very young bulls and cows) (Morin-Doré et al 2020, Wu et al 2020, as well as the exposure to ketone bodies (β-hydroxybutyrate) in post-partum cows, presented evidence that these three conditions share a common metabolic stress (an energy deficit) and have a similar impact on the early embryos: epigenetic alterations, reduction of their own metabolism, and induction of mitochondrial dysfunction (Wu & Sirard 2020). Surprisingly, in vitro culture seems to create a similar picture of embryos being forced into an 'economy mode' as an adaptation to suboptimal metabolic environment.…”
Section: Metaboloepigenetic Events In Early Embryonic Developmentmentioning
confidence: 99%